CREATION OF O. HENRY AND THE NATIONAL LITERARY PROCESS (World Bulletin of Social Sciences, 2024)
In this article, the research of the Uzbek national literary process in the aspect of comparative literary studies creates a basis for determining its place in the field of world literature, its artistic and spiritual level, and its national identity. If we look at it from this point of view, the study of the issue of literary influence is based on scientific views, which provides an opportunity to draw large-scale scientific-theoretical, artistic-philosophical, social-psychological conclusions.